Adaptive nitrogen inputs sustain water‐nitrogen use and improve maize productivity with varied precipitation conditions on a semi‐arid agroecosystem. (11th February 2023) - Liu, Pengzhao; Ning, Fang; Li, Haoyu; Zhang, Yuanhong; Zhang, Qi; Wang, Rui; Wang, Xiaoli; Chen, Xiaoli; Li, Jun
Abstract: BACKGROUND: Maize productivity in semi‐arid regions is increasingly at risk because of the sparse and uneven precipitation, and it is also restricted by excessive or insufficient fertilization management strategies. A 4‐year (2016–2019) field experiment was therefore conducted to show the effects of fertilizer with five nitrogen levels (0, 75–90, 150–180, 270, and 360 kg ha −1, represented as N0, N75‐90, N150‐180, N270, N360, respectively) under two variable precipitation patterns (rainy at pre‐anthesis in 2016 and 2018 versus dry at pre‐anthesis in 2017 and 2019) on soil water storage (SWS), water use efficiency (WUE), nitrogen use efficiency (NUE), and maize yield in the Loess Plateau. RESULTS: Nitrogen inputs increased the amount of above‐ground dry matter and the WUE for dry matter (WUEd). Dry years at pre‐anthesis significantly reduced dry matter accumulation and kernel number per plant. However, soil water storage before sowing (SWSs) decreased from 440 mm in 2016 to 384 mm in 2019, and the increase in fertilization resulted in the water imbalance. Both the maximum grain yield and WUE for grain yield were found in N270 under rainy years at pre‐anthesis, whereas in N150‐180  under dry years at pre‐anthesis. The average nitrogen recovery efficiency (NRE),  nitrogen agronomy efficiency (NAE) and nitrogen partial factor productivity (NPFP) decreased with increases in N application, compared with N360, the NRE, NAE and NPFP of N150‐180 increased by 63.5%, 189.2% and 135.5%, respectively. CONCLUSIONS: Reducing basal N fertilizers could enhance maize yield and maintain moderate water and nitrogen productivity in years with less rainfall. © 2023 Society of Chemical Industry.